Relationship between body mass and clinical response to repetitive transcranial magnetic stimulation (rTMS) for major depressive disorder - Maria Cristina Davila; Brianna Ely; Ann M. Manzardo (Mental Illness)
Repetitive transcranial magnetic stimulation (rTMS) has been proven to be efficacious in the treatment of Major Depressive Disorder (MDD). We previously examined the effectiveness of rTMS for MDD in an applied clinical setting, AwakeningsKC Clinical Neuroscience Institute (CNI) and found high remission rates for patients diagnosed with MDD following rTMS treatment. An unexpected relationship with body composition and rTMS unit was discovered. This sub-study extends the previous investigation through a focused analysis of the effects of body composition on response to rTMS in the treatment of MDD. We utilized data collected from a retrospective review of medical records for patients diagnosed with MDD undergoing rTMS therapy at AwakeningsKC CNI. Patient Health Questionnaire 9 (PHQ-9) scores, time to remission status and body mass index (BMI) at baseline were considered while referencing two different rTMS instruments (MagVenture; NeuroStar). We found 23 (9%) of 247 participants met criteria for obese status (BMI≥30) with an average baseline PHQ-9 score of 22±4, classified as “severe depression”. Obesity status was differentially impacted by the rTMS instrument used for treatment. Patients with obesity showed a shorter time to remission (mean 2.7±0.27 vs. mean 3.4±0.3 weeks) and proportionately greater remission rate (100% vs. 71%) when treated using the MagVenture relative to the NeuroStar instrument. Clinical response to rTMS therapy for MDD appears to be guided by individual factors including body composition and rTMS parameters such as the unit used for treatment. Further study of these influences could aid in the optimization of clinical response to rTMS.